2016
DOI: 10.15761/pd.1000133
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous spinal epidural hematoma in two toddlers: diagnostic pitfalls

Abstract: We report two boys with a spontaneous spinal epidural hematoma (SSEH). The first child presented at the age of 2 years with back pain and general weakness after a respiratory tract infection. After a first surgical intervention he developed a recurrence of bleeding, necessitating re-intervention. He developed medullary ischemia. Important neurologic deficits with paresis of the lower extremities and bladder dysfunction persisted. The other child presented at the age of 1,5 years with irritability and crying, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…SSEH is an infrequent pathology in children, with only 29 cases having been reported. The majority of cases were in the cervical spine (17 out of 29; 58.6%) [3][4][5]. Clinically, the presentation of epidural hematoma in the pediatric age group varies significantly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SSEH is an infrequent pathology in children, with only 29 cases having been reported. The majority of cases were in the cervical spine (17 out of 29; 58.6%) [3][4][5]. Clinically, the presentation of epidural hematoma in the pediatric age group varies significantly.…”
Section: Discussionmentioning
confidence: 99%
“…A review of 29 pediatric cases reported by Pecha and Smeets showed complete resolution of neurological deficits in 15 out of 29 (51.7%) patients, partial resolution in 13 (44.8%) patients, and death in one (3.4%) patient [ 3 , 5 ]. In the present report, the child showed partial recovery after five days from laminectomy and evacuation of hematoma and full recovery was reached after three months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation